Perancangan UI/UX pada Website Laboratorium Energy menggunakan Aplikasi Figma - Tazkiyah, Seila; Arifin, Aridhanyati (Jurnal Teknologi Terpadu, 2022)
Information technology is a technology that serves to help various jobs become more effective and efficient. Making the Energy Laboratory website is one of the applications in information technology. The Energy Laboratory website is an information system used to recapitulate reports and comparative tests and store website-based calibration data for measuring instruments.Â The user interface is created to make the technology accessible for users to use. A good user interface design and experience will keep visitors on the website. But on the other hand, poor interface design and user experience of a website will make users uncomfortable and leave the website. In designing the UI/UX of the Energy Laboratory website, the creation of the interface prototype uses the Figma application. The method used in creating the UI/UX design on the Energy Laboratory website uses the Design Thinking method. The Design Thinking method has five stages: empathize, define, ideate, prototype, and test. The conclusion from this study is that Figma is good and helps in the process of designing the appearance of the Energy Laboratory website with an attractive and easy-to-use User Interface.